(3GdETGQGJ Edi CeGcf GdRjGQGJs - (3YKeGf Hf CMeO Hf eMeO Hf QLH Hf ShjM Hf SYjO GdShjOj GdMhQGfj Ke GdOeTbj,J (B1117 (3g` s ((3EHQGgje Hf SdjeGf Hf eMeO Hf YHO GdYRjR GdMfai GdLjfjfi GdOeTbi s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO , abO SFdJ Cf CLeY eDdakG ai PcQ RjGQGJ OeTb heG MhdgG ef bHhQ GdUMGHI hGdJGHYjf , hGdYdeGA GdYGedjf hGdChdjGA GdUGdMjf s
(3BNQgG (B:s
(3hdjMPQ GdRGFQ Cf jRhQ CMOkG ef GdUGdMjf , hgh ZjQ UGOb ai WdH GdbQH Edi Gddg JYGdi HGdRjGQI hdjcf EgJeGeg ai MGd RjGQJg HLejY MhGSg Ydi PcQ Gddg JYGdi hGdMeO ddg Je cJGH GdRjGQI ddTjN YKeGf Hf CMeO GdMhQGfi Ke GdOeTbi , QMeg Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B18 - (3U(B32s
(3HgG fXGe GdJYbjHIs
(3fbdgG GdfGSN ef fSNI Sbjeis
(3hGUdM ajgG cKjQkG HeQGLYI Gdefbhd Yfgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs